119k views
3 votes
Simplify: 12a4 + (-29a4)​

2 Answers

2 votes

Answer:

-17a⁴

Explanation:

12a⁴ + (-29a⁴) = 12a⁴ -29a⁴ = -17a

User MajorRefactoring
by
5.1k points
2 votes

Answer:

=
-17a^(4)

Step by Step Explanation:

For this question, we must combine like terms.


= 12a^(4) + -29a^(4)


= (12a^(4) + -29a^(4))

Now, we must flip the equation around and subtract.

Keep the variables and exponents where they are.


= -29a^(4) - 12a^(4) = 7a^(4)

We now have our answer.

User Martingw
by
5.5k points